The Middle Oligocene Rock Strata (Tarjil Formation) in Ashdagh Mountain, Sangaw District, Sulaimani Governorate, Kurdistan Region , NE Iraq - Kharajiany, Soran O. A. (Sulaimani Journal for Pure and Applied Sciences, 2013)
The occurrence of Middle Oligocene rocks in Ashdagh Mountain is previously studied like Baba and Bajwan Formations; both of them belong to Middle Oligocene age; the former Formation represents reef- forereef deposits, while the latter one represents reef- backreef deposits. But Tarjil Formation was not studied in the mountain which is complementary of both Baba and Bajwan Formations and represents forereef- open sea- offshore deposits of the same age. The aim of this study is proving the occurrence of Middle Oligocene sedimentary rock of Tarjil Formation.